Silicon-on-Insulator Couplers for SDM Transmission - Pita, Julian L.; Alvarenga, Rafael; Rocha, Lucas; Yang, Jun; Kocabaş, Şükrü Ekin; Li, Ming-Jun; Aldaya, Ivan; Dainese, Paulo; Gabrielli, Lucas H. (My University, 2022)
We present two CMOS-compatible couplers with record-high efficiency for bridging chips and fibers exploiting spatial division multiplexing. The maximum coupling efficiencies to a few-mode and a 7-core fibers were −3.0 dB and −4.3 dB, respectively.